Efectos adversos autoinmunes post vacunacion covid-19 - Alban Loayza, Wilson Ricardo (Machala : Universidad Técnica de Machala, 2022)
Introduction: Vaccines against Covid-19 are currently in a Phase III of experimentation, generating controversies in the safety of being applied due to the appearance of rare autoimmune adverse effects, most reported after the administration of the second vaccination dose. Despite this, the "WHO" states that the benefits outweigh the risks in the population. Objective: To determine the autoimmune adverse effects that are being reported after the administration of the Covid-19 vaccines worldwide through the analysis of high-impact articles in order to capture the aforementioned effects in this research. Methodology: This is a descriptive study based on the compilation of scientific articles with the best evidence published in the last two years, obtained from metasearch engines such as: Pubmed and Elsevier. Conclusion: The autoimmune adverse effects that are known in the short and medium term are the majority produced by the Adenovirus vaccine (AztraZeneca), although the mRNA component vaccines also presented effects such as neurological diseases such as: Guillain Barré, Transverse Myelitis, Paralysis Bell's, Encephalopathy and rare cases of autoimmune pathologies such as: Subacute Thyroiditis, Immune Thrombocytopenia and autoimmune blistering diseases. With AztraZeneca, cases of Venous Thrombosis, Ischemic Cerebrovascular Accidents due to hypercoagulability disorder, Autoimmune Rheumatic Diseases including Vasculitis and SLE (Systemic Lupus Erythematosus), optic neuritis and autoimmune blistering diseases have been reported. All these effects are related to the theory of molecular mimicry produced after the administration of the vaccine.
Introducción: Las Vacunas contra la Covid-19 actualmente se encuentran en una Fase III de experimentación, generando controversias en la seguridad de ser aplicadas debido a la aparición de efectos adversos auto inmunes raros, la mayoría reportados tras la administración de la segunda dosis de vacunación, a pesar de esto la “OMS” afirma que los beneficios superan los riesgos en la población. Objetivo: Determinar los efectos adversos autoinmunes que se están reportando tras la administración de las vacunas Covid-19 a nivel mundial mediante el análisis de artículos de alto impacto con la finalidad de plasmar mencionados efectos en esta investigación. Metodología: Este es un estudio descriptivo basándose en la recopilación de artículos científicos con la mejor evidencia publicados en los dos últimos años, obtenidos desde metabuscadores como: Pubmed y Elsevier. Conclusión: Los efectos adversos autoinmunes que se conocen a corto y mediano plazo son la mayoría producidos por la vacuna de Adenovirus (AztraZeneca) aunque las vacunas de componente de ARNm también presentaron efectos como enfermedades de tipo neurológicas como: Guillain Barré, Mielitis Transversa, Parálisis de Bell, Encefalopatia y raros casos de patologías autoinmunes como: Tiroiditis Subaguda, Trombocitopenia Inmune y Enfermedades ampollosas autoinmunes. Con AztraZeneca se reportaron casos de Trombosis Venosa, Accidentes Cerebro Vasculares Isquemicos debido al trastorno de hipercoagulabilidad, Enfermedades Reumáticas Autoinmunes comprendiendo las Vasculitis y él LES (Lupus Eritematoso Sistémico), neuritis óptica y enfermedades ampollosas autoinmunes. Todos estos efectos están relacionados con la teoría del mimetismo molecular producido posterior a la administración de la vacuna.
Keywords: VACUNAS; COVID-19; EFECTOS ADVERSOS; AUTOINMUNIDAD